Can Ambulatory Blood Pressure Biomarkers Predict Future Falls amongst Older People? - Romero-Ortuno, Roman; Cunningham, Conal; Briggs, Robert; Kenny, Rose (My University, 2025)
Background: While ambulatory blood pressure monitoring (ABPM) biomarkers can predict cardiovascular and cerebrovascular outcomes, little work to date has examined their link with falls. The objective of this study was to examine associations between ABPM biomarkers and further falls in a cohort of older people with recent falls. Methods: A consecutive series (n = 118) of patients≥70 years undergoing falls assessment including 24-hour ABPM were recruited and followed to their next clinical appointment, where incident falls were recorded (minimum follow-up 1 month).ABPM biomarkers included standard deviation for overall systolic blood pressure (sBP), minimum sBP value, sBP values <100 mmHg, sBP dipping (normal dipping>10%, non-dipper 0–10%, reverse dipper <0%) and sBP morning surge (average 2-hour post-awakening sBP minus the lowest night-time sBP). Logistic regression models assessed the relationship between ABPM biomarkers and further falls. Results: One quarter of participants reported a further fall at mean 7 months’ follow-up. Hypotensive episodes were independently associated with further falls, odds ratio 4.52 (95% CI 1.56, 13.11); P = .006). Minimum sBP values were also independently associated with further falls, with a 3% reduction in falls for every 1 mmHg increase in sBP (adjusted odds ratio 0.97 (95% CI 0.94, 0.99); P = .027)). For every increase in morning surge by 1 mmHg, there was a 6% increase in falls (adjusted odds ratio 1.06 (95% CI 1.02, 1.10); P = .005). There was no association between dipping status and further falls. Discussion: ABPM biomarkers may represent important modifiable risk factors for future falls, and ABPM should be integrated into a comprehensive falls assessment in older patients.
PUBLISHED
Keywords: blood pressure; hypotension; blood pressure variability; morning surge; blood pressure dipping; orthostatic hypotension; frailty; older people; Ageing; 24-HOUR AMBULATORY BLOOD PRESSURE MEASUREMENT